Sosialisasi Anti Perundungan pada Siswa Kelas 4C SD Negeri 75 Kota Bengkulu melalui Film Pendek Anti Perundungan (Gerobak Perdamaian) - Lubis, Syahrika Ardiyani; Heriyanti, Lesti; Ledyawati, Ledyawati (Jurnal PKM Manajemen Bisnis, 2024)
Bullying or negotiation is a word that has a meaning as an unpleasant action verbally or non-verbally. In the world of education, negotiation is a dynamic thing because it is a challenge for educators to shape the character of students. This negotiation problem often occurs in the school environment with students as the main actors. Therefore, this research is aimed at examining the socialization carried out on class 4C students at SD Negeri 75 Bengkulu to prevent the behavior of negotiation actions that occur in the school environment. As a result of this negotiation which is also a very detrimental victim, learners who are victims of negotiation are more likely to close themselves, feel insecure, and are not eager to go to school. The method of implementing socialization includes: preparation, implementation and presentation. This socialization is supported by the class teacher because it is considered as one of the character education for students and adds insight to students related to the material. It is expected that students who are victims of negotiations will be more courageous to voice their complaints to their class teachers.